OPTIMIZATION THE GROWTH OF PROTEOLYTIC BACTERIA Bacillus toyonensis AT DIFFERENT SALINITY AND CONCENTRATION OF TOFU WASTEWATER - Oktavia, Dewi Asmiati; Nursyirwani, Nursyirwani; Yoswaty, Dessy (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2022)
Proteolythic bacteria, including Bacillus toyonensis, have potencial to be used in feed industry and in processing of industrial waste. Cultivation of this bacteria requires appropriate enviromental condition and substrate for the growth. The objective of this research was to observe the growth of B. toyonensis at different salinity and tofu wastewater concentration. This experimental research used completely randomized design consisted of two factors. Those were salinity (0‰, 15‰, dan 30‰) and different concentrations of tofu wastewater (8%, 10%, and 12%). Bacterial cell growth was observed by the spectrophotometric method and total plate count (TPC) method. The bacterial cell growth was observed at 0, 24, 48, 72 and 96 hours-incubation. The results indicated that the best medium for the growth B. toyonensis was in tofu wastewater concentration of 12% at salinity of 15‰. The optimum growth occurred at 48 hours-incubation.